Nurse-Driven Universal Concussion Screening: A Quality Improvement Initiative. Issue 1 (January 2021) - Downie, Katie; Cunningham, Aaron; Jafri, Mubeen
Abstract : Background: The purpose of this study was to provide an evaluation of a performance improvement initiative that operationalized universal concussion screening for all pediatric trauma admissions at a Level I pediatric trauma center. Mild traumatic brain injury may be difficult to identify in injured children. We implemented a screening tool to identify the risk for concussion after traumatic injury and to improve access to cognitive evaluation and intervention in children. Prior to implementation of our screening tool, children admitted without obvious head injury or those younger than 12 years were not being screened for concussion risk. Methods: We employed a nurse-driven screening tool, derived from the Centers for Disease Control and Prevention Acute Concussion Evaluation, on all pediatric trauma patients ages 0–17 years. The screening tool identifies symptoms of physical, cognitive, sleep, or emotional deficits and prompts a cognitive evaluation with concussion education. The tool was administered by nursing and tracked in the electronic medical record. Results: Key stakeholders were interviewed to identify workflow barriers and education gaps following implementation. Enhancements to the electronic medical record and refocused nursing education improved compliance from 41% in the first 12 months to 91% at 24 months post-implementation ( p < .001). The increasing number of evaluations additionally resulted in overall more cognitive evaluations as an initial step in identifying and treating previously unrecognized traumatic brain injury. Conclusions: A pediatric concussion screening tool is simple to administer, applies to all developmental ages, and improves diagnostic capture of traumatic brain injury in pediatric trauma when administered by nurses with support through the electronic medical record.